2020
DOI: 10.1136/heartjnl-2020-316586
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipoprotein(a) levels with recurrent events in patients with coronary artery disease

Abstract: ObjectiveWhether lipoprotein(a) (Lp(a)) is a predictor for recurrent cardiovascular events (RCVEs) in patients with coronary artery disease (CAD) has not been established. This study, hence, aimed to examine the potential impact of Lp(a) on RCVEs in a real-world, large cohort of patients with the first cardiovascular event (CVE).MethodsIn this multicentre, prospective study, 7562 patients with angiography-diagnosed CAD who had experienced a first CVE were consecutively enrolled. Lp(a) concentrations of all sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 45 publications
1
34
1
Order By: Relevance
“…Among the 3864 patients with prior MI, 3078 (79.7%) patients were men, and the mean age of the population was 61.7±16.1 years. In the overall population, plasma Lp(a) concentration had a skewed distribution with a tail toward the highest levels, which was consistent with previous studies 20 (as shown in Supplementary Figure S2). Compared to those free of events, those with CVEs were older, more likely to be female, with higher levels of FPG, HbA1c and hsCRP.…”
Section: Baseline Characteristicssupporting
confidence: 91%
See 3 more Smart Citations
“…Among the 3864 patients with prior MI, 3078 (79.7%) patients were men, and the mean age of the population was 61.7±16.1 years. In the overall population, plasma Lp(a) concentration had a skewed distribution with a tail toward the highest levels, which was consistent with previous studies 20 (as shown in Supplementary Figure S2). Compared to those free of events, those with CVEs were older, more likely to be female, with higher levels of FPG, HbA1c and hsCRP.…”
Section: Baseline Characteristicssupporting
confidence: 91%
“…Moreover, new compounds like proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors and antisense oligonucleotide (ASO) targeting hepatic apo(a) are recently reported to reduce circulating Lp(a) levels remarkably, suggesting that the need for a precise characterization of the Lp(a)-associated CV risk is of increasing importance [14][15][16] . To date, Lp(a) has been suggested as a risk predictor in some special populations, such as acute coronary syndrome, stable or premature coronary artery disease (CAD), diabetes mellitus (DM), familial hypercholesterolemia (FH) or postmenopausal women [17][18][19][20][21] . Whether Lp(a) poses additional risk in patients with prior MI is still unclear and the existing studies with small sample size or short-term follow-up did not achieve consistent evidence [22][23][24][25][26][27] .…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…High Lp(a) level has been identified as an independent risk factor of cardiovascular disease with causal links to atherosclerosis. Among patients with known coronary artery disease, it also predicts worse long-term outcomes in terms of allcause death, cardiovascular death, non-fatal myocardial infarction, stroke and in-stent restenosis [48,49].…”
Section: Lipoprotein(a)mentioning
confidence: 99%